Pengaruh Quizizz Dan Motivasi Terhadap Hasil Belajar PAI (Tazakka: Jurnal Pendidikan dan Keislaman, 2025)
Low student learning motivation in PAI learning will affect student learning outcomes. So, effective learning media is needed to overcome this, one of which is using Quizizz media. This research aims to determine the influence of Quizizz media and learning motivation on PAI learning outcomes. The method used was quantitative with a correlational approach, involving 70 students selected through purposive sampling. The data were analyzed using SPSS version 26. The analysis results showed a calculated F value of 0.928, which was lower than the F table of 2.740, with a significance level of 0.400, which exceeded 0.05. The coefficient of determination (R²) of 0.027 shows that Quizizz media and learning motivation only contribute 2.7% to the variation in learning outcomes, while the rest is influenced by other factors. Thus, it can be concluded that Quizizz media and learning motivation do not have a significant influence on Islamic Religious Education learning outcomes.
Keywords: Quizizz; Motivation; Learning Results